The mammalian longevity associated acetylome - S. Feldman-Trabelsi; N. Touitou; R. Nagar; Z. Schwartz; A. Michelson; S. Shaki; M. Y. Avivi; B. Lerrer; S. Snir; H. Y. Cohen (Nature Communications)
Abstract Despite extensive studies at the genomic, transcriptomic and metabolomic levels, the underlying mechanisms regulating longevity are incompletely understood. Post-translational protein acetylation is suggested to regulate aspects of longevity. To further explore the role of acetylation, we develop the PHARAOH computational tool based on the 100-fold differences in longevity within the mammalian class. Analyzing acetylome and proteome data across 107 mammalian species identifies 482 and 695 significant longevity-associated acetylated lysine residues in mice and humans, respectively. These sites include acetylated lysines in short-lived mammals that are replaced by permanent acetylation or deacetylation mimickers, glutamine or arginine, respectively, in long-lived mammals. Conversely, glutamine or arginine residues in short-lived mammals are replaced by reversibly acetylated lysine in long-lived mammals. Pathway analyses highlight the involvement of mitochondrial translation, cell cycle, fatty acid oxidation, transsulfuration, DNA repair and others in longevity. A validation assay shows that substituting lysine 386 with arginine in mouse cystathionine beta synthase, to attain the human sequence, increases the pro-longevity activity of this enzyme. Likewise, replacing the human ubiquitin-specific peptidase 10 acetylated lysine 714 with arginine as in short-lived mammals, reduces its anti-neoplastic function. Overall, in this work we propose a link between the conservation of protein acetylation and mammalian longevity.